Hypersensitivity to sertraline in the absence of hippocampal 5-HT1AR and 5-HTT gene expression changes following paternal corticosterone treatment. Issue 2 (19th July 2018) - Rawat, Arina; Guo, Jackey; Renoir, Thibault; Pang, Terence Y; Hannan, Anthony J
Abstract: The male germ line is capable of transmitting a legacy of stress exposure to the next generation of offspring. This transgenerational process manifests by altering offspring affective behaviours, cognition and metabolism. Paternal early life trauma causes hippocampal serotonergic dysregulation in male offspring. We previously showed a transgenerational modification to male offspring anxiety-like behaviours by treatment of adult male breeders with corticosterone (CORT) prior to mating. In the present study, we used offspring from our paternal CORT model and characterised offspring serotonergic function by examining their responses to the 5HT1A R agonist, 8-OH-DPAT, and the selective serotonin reuptake inhibitor, sertraline. We also examined whether post-weaning environmental enrichment, a paradigm well-known to modulate serotonergic signalling in the brain, had the capacity to normalise the anxiety phenotype of male offspring. Finally, we assessed gene expression levels of 5HT1A R and serotonin transporter in the offspring hippocampus to determine whether deficits in gene transcription contributed to the male-only anxiety phenotype. We report that male and female offspring of CORT-treated fathers are hypersensitive to sertraline but have normal hypothermic responses to 8-OH-DPAT. No deficits in htr1a and sert were found in association with paternal CORT treatment, and environmental enrichment did not rescue the anxiety phenotype of male offspring on the elevated-plus maze. These findings indicate that varying forms of paternal stress exert different effects on offspring brain serotonergic function.